2013
DOI: 10.1055/s-0032-1328189
|View full text |Cite
|
Sign up to set email alerts
|

Lupenone from Erica multiflora Leaf Extract Stimulates Melanogenesis in B16 Murine Melanoma Cells through the Inhibition of ERK1/2 Activation

Abstract: Hypopigmentation diseases are usually managed using UVB light which increases the patients' risk for skin cancer. Here, we evaluated the melanogenesis stimulatory effects of leaf extracts of Erica multiflora, a medicinal plant from the Mediterranean region, and its active component, lup-20(29)-en-3-one, as possible therapeutic agents to address hypopigmentation disorders. B16 murine melanoma cells were treated with E. multiflora extracts or its active component lupenone to evaluate their effects on melanin bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…It has been shown that human placental lipid (25), sesamin (26), quercetin (27), and extracts from Erica multiflora (28) and Pyrostegia venusta (29) can increase melanogenesis in vitro. Thus, these compounds and extracts can be considered as candidates for developing tanning cosmetics and medicines for vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that human placental lipid (25), sesamin (26), quercetin (27), and extracts from Erica multiflora (28) and Pyrostegia venusta (29) can increase melanogenesis in vitro. Thus, these compounds and extracts can be considered as candidates for developing tanning cosmetics and medicines for vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Ba-jiao is a perennial herb, and when we measured the largest part of fresh Rhizoma Musae using a standard ruler, the obtained size (diameter) was used to represent the growth stage. The different growth stages (5,7,10,13,15, and 20 cm) of Rhizoma Musae collected at the same harvest time and origin displayed a range of lupenone and β-sitosterol levels. When the diameter of Rhizoma Musae was approximately 7-13 cm, lupenone content was higher.…”
Section: Quantitative Determination Of Lupenone and β-Sitosterol In Rmentioning
confidence: 99%
“…Current studies have shown that lupenone and β-sitosterol possess multiple pharmacological activities. For example, in vitro studies have found that lupenone stimulates melanogenesis in B 16 murine melanoma cells [10], as well as inhibits α-glucosidase (α-Glu) and protein tyrosine phosphatase 1B (PTP1B) activities [11,12], Furthermore, lupenone inhibits adipogenic differentiation via downregulation of peroxisome proliferator-activated receptor PPARγ expression in 3T3-L1 cells [13]. Additionally, previous studies have reported that β-sitosterol inhibits the growth of HT-29 human colon cancer cells and induces apoptosis of LNCaP human prostate cancer cells in vitro [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…As we can see, EDH demonstrated moderate cytotoxicity in SCC-9 cells in a dose response manner. The concentration resulting in a 50% reduction in cell viability (IC 50 ) after 24 h of treatment was calculated as 448.9 mg/mL (Fig. 1A).…”
Section: Edh Shows Selective Cytotoxicity Against Scc-9 Cellsmentioning
confidence: 99%
“…Lupenone was able to increase tyrosinase mRNA expression via inhibiting the phosphorylation of extracellular signal-regulated kinases 1 and 2 by mitogen-activated protein kinase in B16 murine melanoma cells. 49,50 Additionally, lupenone exhibited weak cytotoxicity against human colorectal cancer (HT-29) and mammary breast cancer (MDA-MB) cell lines. 46,47 b-sitosterol is one of the most common phytosterols in higher plants and presents several pharmacological activities, including anti-tumor activities.…”
Section: Ink4amentioning
confidence: 99%